Effect of UV-B stress on stomatal pore size and pore width in some landscape plants - Sevik, Hakan; Koc, Ismail; Cobanoglu, Hatice; Canturk, Ugur; Kulac, Semsettin (GSC Online Press, 2025)
It is known that global climate change is an irreversible process and will directly or indirectly affect all living things in the world. It is estimated that the most devastating effects of the process will be seen on plants and, especially, woody species that do not have a long life cycle. Therefore, being prepared for the process, determining the extent to which species will be affected, and taking precautions are of great importance in terms of preventing individual, population, and even species losses. This study determined the effects of the increase in UV-B, one of the process's most important effects, on stomatal pore length and pore width. Within the scope of the study, UV-B treatments were made to 10 woody broad-leafed plants at 4 different intensities. At the end of the treatments, leaf samples were obtained from tree species, and images were then taken to scale with the help of an SEM (scanning electron microscope), and stomatal pore length and width were measured. The study results show that the treatments do not significantly affect these characters. However, it is also known that the most important effects of global climate change will be temperature increase and drought. Therefore, it is recommended that similar studies be conducted by including drought stress.
Keywords: Radiation; Ozone; Climate Change; Ultraviolet-B; Stomata